Análise da implementação de um sistema de avaliação baseado em atividades profissionais confiáveis em uma residência pediátrica - Ferreira, Maíra Lucília Monteiro (2022)
Introduction: Assessment based on Entrustable Professional Activities (EPAs) consists of attributing confidence to the learner to perform tasks that represent professional practice, and involves monitoring the learner for a continuous period, with performance analysis, through direct observation, encouragement of self-reflection, and prompt feedback. This set of observations and analysis subsidizes a Clinical Competence Committee (CCC) final decision that assigns a certain level of confidence. The aim of the present study is to analyze the process of improvement of the evaluation system based on EPA in Pediatrics, based on the existing initiative in the medical emergency internship. Methods: In this context, the EPA already used was improved, and standardized, and a CCC was created. The evaluators were trained to apply the new method and the residents were introduced to it. The application of the evaluation method took place for 6 months with residents in the medical emergency internship. At the end of the internship, the CCC created a report for each resident with the result of the evaluation. Subsequently, a questionnaire was applied regarding the perception of residents and evaluators about the changes made during the project, and their data were analyzed. Results: The confidence levels achieved by residents in the CCC were compatible with expected first-year resident knowledge. Regarding the evaluations obtained, there was a reduction over time, which can be improved with resident involvement as an active part of the assessment and also by asking the supervisors fulfill them. In the feedback tool, the most frequent words were “effective communication”, “disease scripts”, “clinical reasoning” and “differential diagnoses”. The perception questionnaire analysis shows that supervisors and residents have a preference for EPA based assessment, considering it as a good form of performance assessment, easy to understand, and useful for learning and feedback. Conclusion: The implementation of an EPA based assessment improves the quality of assessments and results in more assertive feedback. Nevertheless, it can face resistance from the evaluator’s teams and also from the residents. In order to avoid it, one should invest in continuous training sessions. The simplification of the process can be obtained by using online forms with immediate feedback. Other programs are expected to analyze this experience and use it to disseminate EPA-based assessment that is believed to be beneficial to the resident's teaching-learning process.